2015
DOI: 10.1158/0008-5472.can-14-3650
|View full text |Cite
|
Sign up to set email alerts
|

IL13 Receptor α2 Signaling Requires a Scaffold Protein, FAM120A, to Activate the FAK and PI3K Pathways in Colon Cancer Metastasis

Abstract: IL13 signaling through its receptor IL13Ra2 plays a critical role in colon cancer invasion and liver metastasis, but the mechanistic features of this process are obscure. In this study, we identified a scaffold protein, FAM120A (C9ORF10), as a signaling partner in this process. FAM120A was overexpressed in human colon cancer cell lines and 55% of human colon cancer specimens. IL13Ra2-FAM120A coimmunoprecipitation experiments revealed further signaling network associations that could regulate the activity of IL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 25 publications
4
65
0
Order By: Relevance
“…A recent study has shown that CHI3L1 binds to IL-13Rα2, which plays a critical role in its effector responses [4]. It has been also reported that IL-13Rα2 signaling requires a scaffold protein, FAM120A, to activate the FAK and PI3K pathways in colon cancer metastasis [23]. Moreover, IL-13Rα2 utilizes TMEM219 in CHI3L1-induced signaling [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that CHI3L1 binds to IL-13Rα2, which plays a critical role in its effector responses [4]. It has been also reported that IL-13Rα2 signaling requires a scaffold protein, FAM120A, to activate the FAK and PI3K pathways in colon cancer metastasis [23]. Moreover, IL-13Rα2 utilizes TMEM219 in CHI3L1-induced signaling [19].…”
Section: Discussionmentioning
confidence: 99%
“…IL-13Rα2 is significantly upregulated in a number of human cancers [2224] and has been successfully applied as therapeutic target of chimeric antigen receptor (CAR)-engineered T cells in a patient with recurrent multifocal glioblastoma [25]. Although it has been suggested that IL13Rα2-triggered activation of the FAK and PI3K/Akt/mTOR pathways was mediated by FAM120A, activation of Src family kinases and Erk1/2 were not affected by FAM120A silencing [23]. More recently, the membrane protein TMEM219 has been identified as a binding partner of IL-13Rα2.…”
Section: Introductionmentioning
confidence: 99%
“…Short term colonization assays were performed as described previously [24]. In brief, mice were euthanized 4 days after inoculation, and RNA was isolated from lungs using TRIzol Reagent (Invitrogen) and retrotranscribed.…”
Section: Methodsmentioning
confidence: 99%
“…Lyn, as a negative regulator of allergen-stimulated bone marrow-derived mast cells, regulated the expression of the IL-13 gene (Hernandez-Hansen et al, 2005). The binding of IL-13 triggers the recruitment of several molecules, such as PI3K, Akt, and Src kinase, and enables activation of PI3K (Bartolome et al, 2015). We further found that Lyn overexpression significantly repressed IL-13 expression in the lungs of mice exposed to OVA.…”
Section: Discussionmentioning
confidence: 99%